Using English SingSing Channel to Improve Students’ Ability in Generating English Simple Sentences: Penelitian - Alhumairah Juliati, Nr; Nuzulul Isna (PT PUSTAKA CENDEKIA GROUP, 2026)
Developing elementary school students’ ability to construct simple English sentences remains a challenge, highlighting the need for engaging instructional media. This study investigated the effect of the English SingSing YouTube channel on students’ ability to construct simple English sentences. A quantitative approach employing a quasi-experimental posttest-only control group design was used. The participants were 42 fourth-grade students at Al A’raf Elementary School in Southwest Aceh, divided into an experimental group and a control group. Data were collected through a writing test and analyzed using descriptive statistics and an independent-samples t-test. The results indicated that the experimental group achieved a higher mean post-test score (72.86) than the control group (60.48). A significant difference was found between the two groups (p = .004), demonstrating the positive effect of the English SingSing YouTube channel on students’ ability to construct simple English sentences. These findings suggest that the channel is an effective supplementary medium for elementary English instruction.